Cytoplasmic cyclin E predicts recurrence in patients with breast cancer - Hunt, Kelly K.; Karakas, Cansu; Ha, Min Jin; Biernacka, Anna; Yi, Min; Sahin, Aysegul; Adjapong, Opoku; Hortobogyi, Gabriel N.; Bondy, Melissa L.; Thompson, Patricia A.; Cheung, Kwok-Leung; Ellis, Ian O.; et al. (American Association for Cancer Research, 2016)
Background: Low-molecular-weight-cyclin E (LMW-E) detected by Western blot, predicts for reduced breast cancer survival, however, it is impractical for clinical use. LMW-E lacks a nuclear localization signal which leads to accumulation in the cytoplasm that can be detected by immunohistochemistry. We tested the hypothesis that cytoplasmic staining of cyclin E can be used as a predictor of poor outcome in different subtypes of breast cancer using patient cohorts with distinct clinical and pathologic features. Methods: We evaluated the subcellular localization of cyclin E in breast cancer specimens from 2,494 patients from 4 different cohorts: 303 from a prospective study and 2,191 from retrospective cohorts (National Cancer Institute [NCI], MD Anderson Cancer Center [MDA] and the United Kingdom [UK]). Median follow-up times were 8.0, 10.1, 13.5, and 5.7 years, respectively. Results: Subcellular localization of cyclin E on immunohistochemistry was associated with full-length (nuclear) and low molecular weight isoforms (cytoplasmic) of cyclin E on Western blot analysis. In multivariable analysis, cytoplasmic cyclin E staining was associated with the greatest risk of recurrence compared with other prognostic factors across all subtypes in three (NCI, MDA and UK) of the cohorts. In the MDA cohort, cytoplasmic cyclin E staining outperformed Ki67 and all other variables as prognostic factors. Conclusion: Cytoplasmic cyclin E, identifies patients with the highest likelihood of recurrence consistently across different patient cohorts and subtypes. These patients may benefit from alternative therapies targeting the oncogenic isoforms of cyclin E.